2015
DOI: 10.1515/abcsb-2015-0007
|View full text |Cite
|
Sign up to set email alerts
|

Elicitation of Anthocyanin Production in Roots of Kalanchoe blossfeldiana by Methyl Jasmonate

Abstract: The influence of methyl jasmonate on anthocyanin accumulation in roots of Kalanchoe blossfediana plants was studied. Methyl jasmonate (JA-Me), at a concentration of 5.0 to 40.0 mg.l -1 , substantially increased anthocyanin accumulation in roots of intact plants, when it was applied as a solution under natural light conditions. The production of anthocyanin depended on the concentration of methyl jasmonate and the age of the plant. The stimulatory effect was higher in older plants of K. blossfeldiana than in yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…The results obtained by contemporary methods only to a small extent confirm the results of Neyland et al [ 40 ], who detected in the leaves of this plant at the flowering stage the presence of only cyanidin-3-glucoside as the main anthocyanin and small contents of cyanidin-3,5-diglucoside. Previously, in the roots of K. blossfeldiana , eight anthocyanins were found, and quantitatively, the main one was cyanidin 3,5-di-glucoside [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results obtained by contemporary methods only to a small extent confirm the results of Neyland et al [ 40 ], who detected in the leaves of this plant at the flowering stage the presence of only cyanidin-3-glucoside as the main anthocyanin and small contents of cyanidin-3,5-diglucoside. Previously, in the roots of K. blossfeldiana , eight anthocyanins were found, and quantitatively, the main one was cyanidin 3,5-di-glucoside [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, when the leaves were removed, almost no anthocyanin formation was observed. It was later found that JA-Me substantially increased anthocyanin content in the roots of intact K. blossfeldiana plants under natural light conditions [ 43 ]. This means that distinct organs of K. blossfeldiana show varied responses to the action of JA-Me.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These compounds are associated with flower pigmentation of other species belonging to the Kalanchoe genus, together with other anthocyanins, such as peonidin and delphinidin (Nielsen et al, 2005). However, they have also been produced in root cultures (Góraj-Koniarska et al, 2015). The presence of anthocyanins in the leaves of Bryophyllum spp.…”
Section: Identification and Quantification Of Phenolic Compoundsmentioning
confidence: 99%
“…At the same time increased the quantum ef ciency of energy trapping in PSII and ef ciency index was accompanied by decrease in energy dissipation suggesting more effective energy usage. Methyl jasmonate (JA-Me) is an elicitor that causes the formation of anthocyanins in roots of Kalanchoe blossfeldiana (Góraj et al, 2014;Góraj-Koniarska et al, 2015). The anthocyanins are accumulated in roots of intact plants, but not in excised roots.…”
Section: Effect Of Multiwalled Carbon Nanotubes In Common Wheatmentioning
confidence: 99%